PENYARINGAN GALUR HASIL PERSILANGAN TEMBAKAU MADURA DAN ORIENTAL BERDASARKAN INDEKS TANAMAN DAN KADAR NIKOTIN - SUWARSO, SUWARSO; HERWATI, ANIK; HARTTNIADIISDUOSO, SRI; ROCHMAN, FATKHUR; SLAMET, SLAMET; SUPRIYADI, BAMBANG; YASIN, YASIN (Pusat Penelitian dan Pengembangan Perkebunan, 2002)
This expeiment was caried out at Palalang Village, Sub Pakong Distict, Pamekasan District, rom April to October 2000. There were 137 treatments, consisted of 100 FS lines [number 1 to 50 were progeny of Prancak-95 x IW (oriental), number 51 to 100 were progeny of Prancak-95 x IS (oiental)], 36 lines were selected from local cultivar, and Prancak-95 as a check variety. This experiment was arranged in randomized block design, two replications. The objective of this research was to select the promising lines based on crop index and nicotine content. Each lines were morphologically homogen, the potency of yield and quality among lines were significantly different. Foty-four lines were selected. They were resemble to Prancak-95, their nicotine content varied from 1.84% to 4.09%. Genotype and phenotype correlation between nicotine content and yield and grade index were not significantly different. There were 11 selected lines out of the 44 with crop index higher than that of Prancak-95, and their nicotine content vaied from 1.90 -3.96%.